Appendicitis Inflammatory Response Score in Comparison to Alvarado Score in Acute Appendicitis - Jose, Toney; Rajesh, PS (The Surgery Journal, 2021)
Appendicitis is a common differential diagnosis of right lower quadrant pain. Clinical evaluation alone results in high negative appendicectomy rates. Alvarado scoring is the most commonly used clinical prediction rule. The study aimed to compare the recently developed appendicitis inflammatory response (AIR) score with the Alvarado score. This cross-sectional observational study included patients who underwent appendicectomy for clinical suspicion of appendicitis. The clinical and laboratory parameters required for obtaining Alvarado score and AIRS were gathered. Area under ROC curve was calculated for both Alvarado score and AIRS. The study included 130 patients (77 males and 53 females). The negative appendicectomy rate was 10.7%. The perforation rate was 10.3%. The area under ROC for Alvarado score was 0.821 and for AIR score was 0.901. The Alvarado score had a sensitivity of 72% and a specificity of 79% at score ≥6. The appendicitis inflammatory response score had a sensitivity of 98% for scores ≥5 and a specificity of 97% for score ≥6. The C-reactive protein (CRP) value was the best performing individual parameter with an area under ROC of 0.789, followed by WBC count with an area under ROC of 0.762. Appendicitis inflammatory response score is a recently developed score that outperforms the Alvarado score. AIR score has a higher specificity. The sound construction, gradation of parameters, the inclusion of CRP, and avoidance of subjective parameters make the AIR score an attractive clinical prediction rule which can decrease the rate of negative appendicectomy.
Keywords: appendicitis; clinical prediction rule; Alvarado; appendicitis inflammatory response score